2019
DOI: 10.18632/oncotarget.26944
|View full text |Cite
|
Sign up to set email alerts
|

A three-step approach identifies novel shear stress-sensitive endothelial microRNAs involved in vasculoprotective effects of high-intensity interval training (HIIT)

Abstract: Circulatory microRNAs (c-miRNAs) are regulated in response to physical activity and may exert anti-atherosclerotic effects. Since the vascular endothelium is an abundant source of c-miRNAs, we aimed to identify novel vasculoprotective exerciseinduced c-miRNAs by the combined analysis of published endothelial miRNA array data followed by in vivo and in vitro validation. We identified 8 different array-based publications reporting 185 endothelial shear stress-regulated miRNAs of which 13 were identified in ≥3 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…High intensity interval exercise elicits greater shear rate along the vessel wall as compared with a matched bout of moderate continuous exercise (Atkinson, Carter, et al, 2015; Johnson & Wallace, 2012; McManus, Sletten, & Green, 2019). The pattern and magnitude of shear stress is important in regulating endothelial cell expression of miRs (Donaldson et al., 2018; Lee & Chiu, 2019) and it was recently shown that increased shear stress elicits the release of miR from cultured endothelial cells that are also increased in circulation in response to acute exercise ( Schmitz et al., 2019). Other factors that could contribute to changes in arterial stiffness include acute elevations in inflammation and ROS, stimuli known to increase with exercise in an intensity‐dependent manner (Allen, Sun, & Woods, 2015; Johnson et al., 2012; McClean et al., 2015; Vlachopoulos et al., 2005; Vucinovic et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High intensity interval exercise elicits greater shear rate along the vessel wall as compared with a matched bout of moderate continuous exercise (Atkinson, Carter, et al, 2015; Johnson & Wallace, 2012; McManus, Sletten, & Green, 2019). The pattern and magnitude of shear stress is important in regulating endothelial cell expression of miRs (Donaldson et al., 2018; Lee & Chiu, 2019) and it was recently shown that increased shear stress elicits the release of miR from cultured endothelial cells that are also increased in circulation in response to acute exercise ( Schmitz et al., 2019). Other factors that could contribute to changes in arterial stiffness include acute elevations in inflammation and ROS, stimuli known to increase with exercise in an intensity‐dependent manner (Allen, Sun, & Woods, 2015; Johnson et al., 2012; McClean et al., 2015; Vlachopoulos et al., 2005; Vucinovic et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of specific ci‐miRs correlate with arterial stiffness in humans (Deng et al., 2017; Parthenakis et al., 2017; Van Craenenbroeck et al., 2016). Additionally, in vitro and animal experiments have shown that changes in specific vascular stimuli such as shear stress and inflammation affect the expression and release of microRNAs from vascular cells, suggesting these molecules may play roles in exercise intensity‐dependent changes in arterial stiffness (Alexy, Rooney, Weber, Gray, & Searles, 2014; Donaldson et al., 2018; Hale et al., 1843; Lee & Chiu, 2019; Schmitz et al., 2019; Zhou et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The two HIIT protocols were matched for total workload and duration (Table 1; Schmitz et al, 2019c). Respective metabolic equivalents (METs) were estimated according to the Compendium of Physical Activities (Ainsworth et al, 2000) with 8.0 METs for running at 8 km h −1 (code 12030, for active recovery) and 19.0 METs for running at all-out speed (code 12132) as reported previously .…”
Section: High-intensity Interval Training and Determination Of Repeatmentioning
confidence: 99%
“…Besides other molecular factors, miRNAs and microparticles have the potential to spread molecular signalling throughout the body via the vascular system. miRNAs (such as microRNAs -16, -21, and -126) attenuate endothelial inflammation and may mediate vascular-protective effects of physical exercise including HIT [54,55].…”
Section: Accepted Manuscriptmentioning
confidence: 99%